Mechanism and reaction kinetics analysis of small-molecule gas formation during thermal decomposition of hydroxylamine nitrate - Men Li; Tianpeng Li; Xinbao Gao (Alexandria Engineering Journal)
Hydroxylamine nitrate (HAN) is a new type of high-energy oxidant used in controllable propulsion. The present study explores the reaction mechanism of HAN using density functional theory and constructs reaction mechanism diagrams to understand the mechanism of small-molecule gas formation during the thermal decomposition of HAN. Based on transition state theory, the half-life of each reaction is calculated under standard conditions and the kinetic parameters of each reaction are scanned across the temperature range 298.15–1200 K. The research revealed a vast half-life time scale forreaction of NO generation, NO2 generation, NO+NO2 generation, N2O generation and N2 generation process, meaning thatthese reaction can not occur. The half-life of RDS5 is very short. However, the reaction is also limited by the concentration of the reactant HNO. However, increasing the temperature rapidly decreases the reaction half-life and the reaction can easily proceed. Taking 300 s as the easily reactive boundary point, the cut-off points of the rate-determining steps of Processes 1 (NO generation), 2 (NO2 generation), 3 (NO + NO2 generation), 4 and 5 (N2O generation) and 6 (N2 generation) are 466 K, 468 K, 576 K, 587 K and 402 K, respectively. The calculated reaction mechanism revealed two isomeric transformations of HNO2 and H2N2O2 and three isomeric transformations of H2N2O. Both HNO2 and H2N2O2 are transformed via H-atom transfer, while H2N2O is transformed either by H-atom transfer or intramolecular rotation. As the formation reaction of NO2 does not have the lowest free energy, the NO2 product is easily converted to other products. When NO2 coexists with NO, it is also easily converted to the stable products N2O, N2 and NH3.